Boric Acid as Highly Efficient Catalyst for the Synthesis of Phenols from Arylboronic Acids. Issue 2 (30th January 2014) - Gogoi, Kongkona; Dewan, Anindita; Gogoi, Ankur; Borah, Geetika; Bora, Utpal
ABSTRACT A simple, efficient, and environmentally benign boric acid catalyzed methodology for the ipso‐hydroxylation of arylboronic acid to phenol has been developed using aqueous hydrogen peroxide as an oxidizing agent and ethanol as the solvent. The versatility of this protocol is that the reactions were performed at room temperature in short reaction time under metal‐, ligand‐, and base‐free conditions.